Peranan Perpustakaan Sekolah Terhadap Minat Baca Siswa di SDN 2 Cupel - Negara, I Wayan Satria Abdi; Dewi, Made Sri Astika; Dharma, I Made Aditya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The school library as a means of supporting students, provides a variety of information according to the needs of its users. The purpose of this study is to find out how the role of the school library in increasing students' reading interest at SDN 2 Cupel. The research method used is descriptive research with a qualitative approach. Data collection techniques used are questionnaires and online interviews. The dataanalysis technique is using data reduction. The results obtained after collecting the results ofquestionnaires and interviews were found that the role of the school library in increasing student interest in reading at SDN 2 Cupel was not maximized due to many factors including the lack of supporting facilities and infrastructure in the library.